1991
DOI: 10.3109/08977199109000289
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Stimulates Glomerular Mesangial Cell Proliferation Through a Protein Kinase C-Independent Pathway

Abstract: Basic Fibroblast Growth Factor (bFGF) is shown to be a potent mitogen for cultured glomerular mesangial cells. bFGF induces an increase in cell number and stimulates DNA synthesis measured by [3H]thymidine incorporation in normal as well as in protein kinase C-depleted cells. The ED50 observed in both cases are nearly identical (approximately 0.04 nM) and maximal responses are obtained at 1 nM. Staurosporine, a potent protein kinase C inhibitor, does not prevent bFGF from inducing mitogenesis. On the contrary,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…This observation, coupled with the inability of PKC inhibitors to abrogate the bFGF-mediated elevation in ODC mRNA expression in malignant cells, suggests that the bFGF-mediated alterations in ODC mRNA expression in highly malignant H-ras transformed fibrosarcoma cells occurs through a protein kinase C-independent pathway. These observations are in keeping with several studies which suggest that the mitogeniclproliferative effects of FGFs may not be mediated by protein kinase C activation [Chambard et al, 1987;Issandau and Darbon, 1991;Kaibuchi et al, 1986;Magnaldo et al, 19861. The exact nature of the signal transduction pathway involved in these malignant H-rus transformed cells remains to be further elucidated.…”
Section: Discussionsupporting
confidence: 87%
“…This observation, coupled with the inability of PKC inhibitors to abrogate the bFGF-mediated elevation in ODC mRNA expression in malignant cells, suggests that the bFGF-mediated alterations in ODC mRNA expression in highly malignant H-ras transformed fibrosarcoma cells occurs through a protein kinase C-independent pathway. These observations are in keeping with several studies which suggest that the mitogeniclproliferative effects of FGFs may not be mediated by protein kinase C activation [Chambard et al, 1987;Issandau and Darbon, 1991;Kaibuchi et al, 1986;Magnaldo et al, 19861. The exact nature of the signal transduction pathway involved in these malignant H-rus transformed cells remains to be further elucidated.…”
Section: Discussionsupporting
confidence: 87%
“…Optimal activities of FGF2 require glypicans, 72 including GPC5. 73 Although FGF2 stimulated proliferation of glomerular mesangial cells, endothelial cells, and podocytes, 71,74,75 an excess amount of FGF2 was harmful to glomeruli and induced proteinuria. 76,77 Podocyte-specific knockdown of GPC5 has also reduced FGF2-induced podocyte injury and proteinuria by inhibiting FGF2 binding to cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found that SP-600125 at a dose of up to 20 M had no significant effect on LDH release, thus ruling out the cytotoxicities of the compound under current experimental conditions. It is well recognized that MC proliferation can be stimulated by activation of tyrosine kinase receptors for epidermal growth factor (EGF) (7,36), platelet derived growth factor (PDGF) (1,7), and bFGF (8,17), and of G protein-coupled receptors for ANG II (2, 16) and endothelin-1 (33,34). The signaling transductions elicited by activation of tyrosine kinase receptors and G protein-coupled receptors converge at Erk1/2.…”
Section: Discussionmentioning
confidence: 99%